The Influence of the Madrasah Principal's Transformational Leadership on Teacher Work Motivation (Studies at Madrasah Aliyah Manbaul Ulum Wonosari bondowoso ) - Rochmaniah, Siti; Zaini, Zainuddin Al Haj; Abidin, Zainal (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Advanced educational institutions are very dependent on the role of the school or madrasah principal who has . Teachers and Employees have a desire to be led by certain people who have a clear vision of goals, understand how to realize goals and try to teach them. The role of the madrasa head is very urgent in boosting employee motivation. Leader characteristics influence the work climate in an educational institution. This study was designed to test whether transformational leadership has a significant effect on work motivation. The research method uses a quantitative approach. MA Manbaul research sample Ulum Wonosari Bondowoso , data collection was carried out by distributing 82 questionnaires. The analysis technique uses simple linear regression analysis . Based on the simple linear regression analysis used, the results show that transformational leadership has a significant positive effect on employee motivation